Sometimes I think about dying [videorecording (DVD)] - Armento, Kevin; Horowitz, Stefanie Abel; Wright-Mead, Katy; Ridley, Daisy, 1992-; Merheje, Dave; Cheena, Parvesh, 1979-; Debonis, Marcia; Stalter, Megan; O'Grady, Brittany; Elrod, Bree; Lane, Dustin; Morris, Dabney (Oscilloscope Laboratories, 2025)
Fran, who likes to think about dying, makes the new guy at work laugh, which leads to dating and more. Now the only thing standing in their way is Fran herself.